2019
DOI: 10.1016/j.mayocp.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Renal Elimination of Drugs With Cystatin C vs Creatinine: A Systematic Review

Abstract: Serum cystatin C has been proposed as a kidney biomarker to inform drug dosing. We conducted a systematic review to synthesize available data for the association between serum cystatin C and drug pharmacokinetics, dosing, and clinical outcomes in adults (!18 years). PubMed, Ovid MEDLINE, Ovid EMBASE, EBSCO CINAHL, and Scopus were systematically searched from 1946 to September 2017 to identify candidate studies. Studies of cystatin C as a predictor for acute kidney injury or for management of contrast-associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
62
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 47 publications
4
62
0
5
Order By: Relevance
“…Other drugs evaluated included digoxin, dabigatran, perindopril, carboplatin, and topotecan. Overall, eGFR cysC predicted observed drug clearance and serum concentrations of medications as well as, if not better than, SCr in the majority of the identified studies [25]. The literature was most robust for vancomycin, which was evaluated in 12 studies that included 1806 patients [26][27][28][29][30][31][32][33][34][35][36].…”
Section: Medication Dosing Based On Cyscmentioning
confidence: 98%
See 4 more Smart Citations
“…Other drugs evaluated included digoxin, dabigatran, perindopril, carboplatin, and topotecan. Overall, eGFR cysC predicted observed drug clearance and serum concentrations of medications as well as, if not better than, SCr in the majority of the identified studies [25]. The literature was most robust for vancomycin, which was evaluated in 12 studies that included 1806 patients [26][27][28][29][30][31][32][33][34][35][36].…”
Section: Medication Dosing Based On Cyscmentioning
confidence: 98%
“…The association between cysC and the corresponding eGFR and drug pharmacokinetics has been described in a number of studies [25]. A systematic review that explored the predictive relationship between cysC and drug clearance identified 28 studies published between 2004 and 2017 that included 3455 patients treated with 16 different renally-eliminated medications [25]. Antimicrobials were the most commonly studied and included vancomycin, aminoglycosides, beta-lactams, tenofovir, and teicoplanin.…”
Section: Medication Dosing Based On Cyscmentioning
confidence: 99%
See 3 more Smart Citations